China's Second Revolution: Reform after Mao - Harding, Harry (Rowman & Littlefield Publishers, 2010)
China has, since 1976, been enmeshed in an extraordinary program of renewal and reform. The obvious changesthe T-shirts, blue jeans, makeup and jewelry worn by Chinese youth; the disco music blaring from radios and loudspeakers on Chinese streets; the television antennas mushrooming from both urban apartment complexes and suburban peasant housing; the bustling free markets selling meat, vegetables and clothing in China's major citiesreflect a fundamental shift in the government's policy toward the economy and political life. Although doubts about the long-term commitment to reform arose after the student protests in December 1986 and the dismissal of Party General Secretary Hu Yaobang in January 1987, the scope of reform has been so broad and the pace of change so rapid, that the post-Mao era fully warrants Den Xiaoping's description of it as the "second revolution" undertaken by the Chinese Communist Party.